Evaluation of silk fibroin protein/poly(vinyl alcohol) transparent membranes as prospective patch for acne care. (September 2015) - Bai, Meng-Yi; Hsueh, Yi-Wen
In this work, the drop-casting method was used to mix silk with poly(vinyl alcohol) to generate a composite membrane silk fibroin protein/poly(vinyl alcohol) transparent membrane, whose porosity and permeability can be controlled by adding (or not adding) NaCl, for increasing its permeability. The silk fibroin protein/poly(vinyl alcohol) transparent membranes did not exhibit significant cytotoxicity when an appropriate amount of tea tree oil was added. When the volume of tea tree oil that was added to the non-porous silk fibroin protein membrane or porous silk fibroin protein membrane increased above 12.50 µL/patch, the viability of 3T3 fibroblast cells began to fall to below 80%. Accordingly, 3.12, 6.25, and 12.50 µL were added in the following anti-bacterial, anti-inflammatory, and in vivo animal studies. Although the silk fibroin protein/poly(vinyl alcohol) transparent membrane exhibits a slight anti-bacterial and anti-inflammatory effect, when an appropriate amount of tea tree oil was added, our membranes show great enhancement in inhibition of formation of NO in lipopolysaccharide-induced macrophages (Raw 264.7) and the following anti-bacterial ability. In the experiments on the inhibition of the proliferation of Propionibacterium acnes, the silk fibroin protein/poly(vinyl alcohol)transparent membrane exhibited a mild anti-bacterial effect (with a bacteriosis ratio of ~78%), but when 3.12–12.50 µL tea tree oil was added, the inhibition ratio reached approximately 84%–99%. In the evaluation of the animal model, we found that increasing the numbers of treatment days markedly increased the inhibition of P. acnes in the experimental group.